UTILIZATION OF VOLUME COMPOSITE FRACTION IN KEPOK BANANA STEM (MASSA PARADISIACA) RANDOM CORNER ORIENTATION WITH POLYESTER MATRIX AGAINST THE MECHANICAL CHARACTERISTIC - Widodo, Basuki; Subardi, Anang (Journal of Sustainable Technology and Applied Science (JSTAS), 2020)
This study aims to determine the effect of volume fraction (10%, 20%, 30%, 40%, 50%) of composite banana stem fiber with polyester matrix on tensile strength and impact strength. From the results of the study obtained an average strength value the most optimal tensile is found in the 10% fiber volume fraction and 90% matrix that is 51.863 N/mm2 and strain value 5.754 N/mm2. As for the lowest tensile strength at 20% fiber volume fraction and 80% matrix that is 36.356 N/mm2 and strain value 7.796%. The composite which has the highest average energy and impact value is the 50% volume fraction matrix 50% has an absorption rate with an average absorbed energy value of 0.8093 Joules and an average Impact Price of 0.0101 Joules / mm2, while the lowest in the volume fraction of 20%, 80% matrix with an average energy value of 0.4129 Joules and an average Impact Price of 0.0052 Joules/mm2. It can be concluded that the addition of fiber volume fraction affects the tensile strength and impact strength.